Complete genome sequence of Pasteurella multocida subsp . septica isolated from a sepsis patient in Thailand - Supawee Kinnonkok; Kiatthida Tinthalang; Jenjira Rujidamp; Supphachoke Khemla; Barameht Piralam; Orapan Sripichai; Pisut Pongchaikul (Microbiology Resource Announcements, 2026)
ABSTRACT Pasteurella multocida is a rare cause of human infection most often associated with animal bites or scratches. We report the complete genome sequence of Pasteurella multocida subsp. septica strain 0092 recovered from the blood culture of a sepsis patient in Nakhon Phanom, Thailand in 2022. The genome totals 2,392,800 bp.